Elemen dalam buku indie: satu kajian grounded theory terhadap mahasiswa Universiti Pendidikan Sultan Idris - Muhammad Atiullah Othman,; Nadarajan Thambu,; Siti Noranizahhafizah Boyman, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Indie books are produced by writers who believe in “absolute freedom in writing”. In Malaysia, the Indie books, which uses non-standard language, contains inverse thoughts and often breaks out from the Sunnah wal Jamaah teachings, condemned and perceived as a work against the mainstream. However, the Indie Book has received a warm welcome from the younger generation. Therefore, the objective of this study is to identify the students’ understanding of the moral content contained in the Indie Book, to explain the students’ reaction to the moral content in Indie Books and to explore main elements behind the writing of this book. This study uses a qualitative approach using document analysis techniques and interviews to collect data. The results of this study show support positive features such as da’wah and motivational elements. In addition, the negative features found in the Indie Books are very disturbing because they contain obscene, violent and ideological elements that deviate from the state’s rule. However, the students were found to be interested in Indie Books because it‘s contain key elements of attraction. This key element is freedom, realistic and relaxed as well as key feature of Postmodernism and Existentialism.